Permasalahan dalam Optimalisasi Pengadaan Barang dan Jasa Pemerintah yang Efektif dan Efisien - Adri, Saidil (LPPM Universitas Putera Batam, 2024)
Procurement of goods/services is an activity of procuring goods/services carried out by Ministries/Regional Apparatus Institutions funded by the APBN/APBD through several processes. The size of the government budget used in procurement of goods/services, namely around 40%, will influence government spending and government work programs. The purpose of writing this article is to find out the problems in the process of procuring goods and services. This research is a library research, where the data that supports the study comes from library sources in the form of books, encyclopedias, journals, magazines, newspapers, and so on. The results of this research article are that regulations relating to PBJ are still weak, especially in the implementation mechanisms, so that the quality of the goods produced is not appropriate, there is corruption, collusion and nepotism (KKN) between officials and providers, which are still often found in making plans, there is a lack of clarity between needs. vs desires, the problem with determining goods/services is that it does not take into account the BMN inventory so that it has an impact on wasting resources, budget and RUP, the supporting budget is not enough, this will have an impact on activities being hampered, and PBJ targets being hampered, and the implementation of the election not being utilized effectively. maximum for clarification and equalizing perceptions, this will have an impact on failed tenders and public distrust